Growth, expectations and tariffs - Seppo Honkapohja; Arja H. Turunen-Red; Alan D. Woodland (Bank of Finland, 2011)
We study a many-country endogenous growth model in which decisions about innovation and new investment are influenced by growth expectations. Adaptive learning dynamics determine the country-specific short-run transition paths. The countries differ in basic structural parameters and may impose tariffs on imports of capital goods. Numerical experiments illustrate the adjustment dynamics that follow the use of tariffs. We show that countries that limit trade in capital goods can experience dynamic gains both in growth and in utility and that such gains persist longer the larger the structural advantages of the region that applies tariffs. Substantial differences in levels of innovation, consumption, output and utility can appear, and asymmetries in economic outcomes that were present before trade restrictions are made more severe.
URN:NBN:fi:bof-20140807338
Keywords: 330